2016
DOI: 10.1155/2016/7957825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polypharmacy on the Rehabilitation Outcome of Japanese Stroke Patients in the Convalescent Rehabilitation Ward

Abstract: Background. A risk factor associated with stroke onset is chronic kidney disease (CKD). To prevent stroke reoccurrence, it is necessary to strictly manage blood pressure, lipids, and plasma glucose. Therefore, some cases are forced to polypharmacy, elderly patients in particular. Polypharmacy often leads to adverse drug reactions and has the potential to negatively affect the rehabilitation of stroke patients. The aim of the present study was to investigate the effects of polypharmacy using a functional indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The inclusion criteria were age ≥65 years and history of cerebral infarction, cerebral haemorrhage, or subarachnoid haemorrhage. The exclusion criteria were age <65 years, diagnosis with other cerebrovascular diseases, patients with missing data, and patients with a history of dementia, because it has been shown to preclude assessment of cognitive change in the FIM . Participants were divided based on presence or absence of increased anticholinergic load from admission to discharge to “ARS increase group” and “ARS non‐increase group.”…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion criteria were age ≥65 years and history of cerebral infarction, cerebral haemorrhage, or subarachnoid haemorrhage. The exclusion criteria were age <65 years, diagnosis with other cerebrovascular diseases, patients with missing data, and patients with a history of dementia, because it has been shown to preclude assessment of cognitive change in the FIM . Participants were divided based on presence or absence of increased anticholinergic load from admission to discharge to “ARS increase group” and “ARS non‐increase group.”…”
Section: Methodsmentioning
confidence: 99%
“…A study size analysis was performed using Power and Sample Size Calculation Software (version 3.0, 2009, William D. Dupont, PhD, and Walton D. Plummer, Department of Biostatistics, Vanderbilt University; available from http://biostat.mc.vanderbilt.edu/wiki/Main/PowerSampleSize). A previous study in Japan indicated that the mean FIM gain of stroke patients in convalescent rehabilitation wards was 19.7 ± 18.5, from which we inferred that there was an overall decrease of 6 in the FIM gain because of polypharmacy . To detect a mean difference of 6 in the FIM gain (with a standard deviation of 18.5) among two groups at a ratio of 1:1, we required 150 patients per group to achieve a power (1‐β) of 0.8 and an α of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypharmacy and inappropriate prescribing recently have been drawing attention in the rehabilitation area. Among 144 stroke patients with chronic kidney disease in a convalescent rehabilitation ward, 48 (33.3%) patients took six or more drugs and were categorized into a polypharmacy group . Improvement of activities of daily living in the polypharmacy group, as assessed by the motor Functional Independence Measure efficiency, was significantly lower than in the nonpolypharmacy group .…”
mentioning
confidence: 99%
“…Among 144 stroke patients with chronic kidney disease in a convalescent rehabilitation ward, 48 (33.3%) patients took six or more drugs and were categorized into a polypharmacy group . Improvement of activities of daily living in the polypharmacy group, as assessed by the motor Functional Independence Measure efficiency, was significantly lower than in the nonpolypharmacy group . Moreover, taking potentially inappropriate medications as evaluated by the 2015 American Geriatrics Society Beers Criteria was independently and negatively correlated with motor Functional Independence Measure gain in older stroke patients in a convalescent rehabilitation ward .…”
mentioning
confidence: 99%